RESEPSI QUR’AN SURAH AL-FATIHAH DALAM LITERATUR KEISLAMAN PADA MASA ABAD PERTENGAHAN - Mushthoza, Zidna Zuhdana; Yahya, Ahmad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThis research focuses on the study of